Russian Attitude from Iranian Nuclear Program (Journal of the College of Education for Women, 2019)
The subject of Iranian no clear program and the Russian Attitude from it, regard as an important matter in international relations, really it was remarkable and distinctive position towards.The development of Iranian no clear program in this study we treated Three sides.The firs the collapse of USSR and its effect of Iran while the second aspect concentrate on the nature of Iranian- Russia Relation, the Third side research the Russia A attitude fromIranian nuclear program, briefly this attitude is represented by positive, supporting and predication but in the sometime focused on Russian interests in the region of Middle East.